(untitled) (Journal of history, 2024)
Studying the historical and geographical aspects of the Golden Horde helps preserve its cultural heritage and expands knowledge about the past, which contributes to understanding the cultural diversity of the world. The purpose of the study was to identify historically significant data on the geography and political organization of the Golden Horde based on the analysis of the encyclopedia by al-Kalkashandi. To achieve this goal, an integrated approach was used, including a critical analysis of the text "Subh al-asha fi sina’at al-insha" using historical-critical, intertextual and comparative methods. As a result of the conducted research, the main geographical characteristics of the key cities and regions of the Golden Horde, such as Sarai, Hadji Tarkhan, Sauran and others, were identified, which made it possible to more accurately represent their size, structure and interrelationships with each other. In addition, the study examined the territorial boundaries of the Golden Horde, including its influence on neighboring regions, which allowed us to get a more complete picture of the geopolitical situation. The analysis of al-Kalkashandi’s work also revealed the ethnocultural composition of the state’s population, including various ethnic groups, their distribution across the territory and interaction with each other. This gave an understanding of the socio-cultural dynamics of the Golden Horde and the key moments in its historical development. The results of the study also revealed the main trade routes, trading partners and goods that were of great value to the Golden Horde, which allowed for a better understanding of its economic situation and role in international trade at that time. The results highlight the importance of al-Kalkashandi’s work as a valuable source for studying the history of the Golden Horde, as well as expand knowledge about the geography and history of this region, helping to recreate a more accurate picture of its political, economic and cultural life. Key words: territorial boundaries, location, ethnocultural composition, political structure, cultural heritage.